Barriers to learning for sustainability: a teacher perspective - Sally Parry; Ellen Metzger (Sustainable Earth Reviews)
Abstract We collectively face a constellation of complex and interconnected problems that threaten human and planetary wellbeing now and into the future. Holistic, multidisciplinary education that integrates the social, environmental and economic pillars of sustainability and enables learners to contribute to more sustainable societies are widely expected to play a crucial role in addressing these challenges. However, transformative learning to foster more sustainable ways of living cannot take place without teachers, who serve as role models for students and are widely acknowledged as key agents of social change. Teachers are called upon to translate international policies for sustainability education into classroom practice, but research shows that many practicing educators feel unprepared to help learners develop the competencies needed to forge more sustainable paths forward. In this commentary, the reflections of a British science teacher provide a first-hand account of the disconnect between international policy on sustainability education and the lived experiences of a classroom teacher and serve as a launch point for comparison with other teachers’ perspectives on teaching and learning for sustainability as documented in the literature. Despite significant context-based differences in how sustainability education is implemented, teachers’ voices from across the world reveal several common obstacles to multidisciplinary, learner-centered education for sustainability, including disciplinary silos, a focus on high stakes assessments, and inadequate professional learning opportunities for future and practicing educators. These hurdles persist despite repeated calls from policy-makers and researchers to better prepare and support educators as the facilitators of learning for sustainability, underscoring the need to more closely connect top-down Education for Sustainable Development policy to teachers’ needs and classroom experiences.